Stability Profile and Clinical Evaluation of an Innovative Hydrogel Containing Polymeric Micelles as Drug Delivery Systems with Oregano Essential Oil against Fibroepithelial Polyps - Bora, Larisa; Iftode, Andrada; Muț, Ana Maria; Vlaia, Lavinia Lia; Olteanu, Gheorghe-Emilian; Muntean, Delia; Dehelean, Cristina Adriana; Buda, Valentina; Coneac, Georgeta Hermina; Danciu, Corina (Pharmaceuticals (Basel, Switzerland), 2023)
Skin tags, also known as fibroepithelial polyps (FPs) or acrochordons, are soft, pigmented excrescences, with a prevalence of 50–60% in the population, occurring especially in the fourth decade of life. To date, FPs have been efficiently eliminated using minimum invasive methods such as surgical removal, cauterization, laser irradiation, and cryosurgery. Over-the-counter treatments are also of interest for patients due to their non-invasive character, but their clinical efficiency has not been clearly demonstrated. This study was designed in order to evaluate the efficacy of a modern-pharmaceutical-formulation-type poloxamer-based binary hydrogel, having Origanum vulgare L. essential oil (OEO-PbH) as an active ingredient in the management of FPs. The formulation has been shown to possess good qualities in terms of stability and sterility. Non-invasive measurements revealed changes in some physiological skin parameters. An increase in transepidermal water loss (TEWL) and erythema index was noted, while skin surface water content (SWC) decreased during eight weeks of treatment. The macroscopic evaluation revealed that the FPs dried and shrunk after topical treatment with OEO-PbH. Clinically, patients presented a lowering of the number of lesions on the treated area of 20–30% after one month of treatment and around 50% after the second month. Histopathological examination suggests that topical treatment with OEO-PbH may induce histological changes in the epidermis, dermis, and fibrovascular cores of FPs, including a loss of thickness, reduced size and number of blood vessels, and low cellularity. These changes may contribute to the observed reduction in size of FPs after treatment with OEO-PbH.